Intrauterine Device Malposition Into The Bladder with Stone Formation - Kuncoro Adi; Gugum Indra Firdaus (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran)
Introduction: Intrauterine device (IUD) is accepted and used as an effective contraception globally. Malposition of intrauterine device into the bladder with stone formation was very rare complication. In this study, we report a case in which IUD malposition had caused bladder stone formation in a female patientCase presentation: Patient was a female, 50 years old, complained of painful urination approximately 1 year before admission and was diagnosed with recurrent urinary tract infection (UTI). Patient also had history of IUD insertion for ten years. Instead of IUD insertion in her uterine, patient had history of 2 times birth delivery. Imaging examination was performed on April 2018, in Hasan Sadikin Hospital, Bandung and found IUD in pelvic area. In ultrasound imaging we found a hyperechoic with acoustic shadow that resembles an IUD. Endoscopic management was performed by cystoscopy instrument. We found a half of IUD in the bladder with encrustation and calcification in the device. We performed lithotripsy with pneumatic lithotripter to disintegrate the encrustation. An IUD extracted from the bladder cavity by cystoscopy grasper. Postoperative evaluation we found no complications and send home the patient 3 days after the procedure. Conclusion: IUD malposition can be found to bladder cavity. Recurrent UTI needs radiological investigation to provide for any abnormality in urinary tract. IUD extraction could be performed by transvesical approach if the device malposeed to the bladder. Key words: bladder stone, intrauterine device, malpositionAbstrakPendahuluan: Intrauterin device (IUD) merupakan alat kontrasepsi yang efektif dan diterima serta digunakan secara luas. Malposisi IUD ke buli dengan pembentukan batu adalah komplikasi yang sangat jarang terjadi. Pada studi berikut ini, kami melaporkan sebuah kasus malposisi IUD yang telah menyebabkan pembentukan batu buli pada pasien perempuan. Presentasi kasus: Seorang perempuan usia 50 tahun mengeluh nyeri ketika sedang berkemih sejak 1 tahun sebelum masuk rumah sakit dan didiagnosis dengan infeksi saluran kencing berulang. Pasien memiliki riwayat pemasangan IUD sejak 10 tahun lalu. Walaupun demikian, pasien memiliki riwayat 2 kali melahirkan. Pada pemeriksaan rontgen ditemukan IUD di rongga pelvis. Pada pemeriksaan ultrasonografi ditemukan gambaran hiperekhoik dengan acoustic shadow dengan bentuk menyerupai IUD. Tata laksana endoskopik dilakukan dengan alat sistoskopi. Kami menemukan sebagian IUD berada di dalam buli disertai dengan enkrustasi dan kalsifikasi pada IUD. Kami melakukan litotripsi dengan litotriptor pneumatik untuk menghancurkan enkrustasi. Intrauterine device dikeluarkan dari dalam buli dengan pinset sistoskopi. Evaluasi pascaoperasi tidak ditemukan komplikasi dan pasien pulang 3 hari setelah prosedur.Simpulan: Malposisi IUD dapat terjadi ke dalam buli. Infeksi saluran kemih berulang memerlukan pemeriksaan radiologis untuk mencari abnormalitas pada saluran kemih. Intrauterine device dapat dikeluarkan dengan pendekatan transvesika jika mengalami malposisi ke buli. Key words: batu buli, intrauterine device, malposisi